2021
DOI: 10.1021/acs.jpcb.1c01797
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of the Dengue Virus Protease Revealed by Fluorescence Correlation and Single-Molecule FRET Studies

Abstract: The dengue virus protease (DENV-PR) represents an attractive target for counteracting DENV infections. It is generally assumed that DENV-PR can exist in an open and a closed conformation and that active site directed ligands stabilize the closed state. While crystal structures of both the open and the closed conformation were successfully resolved, information about the prevalence of these conformations in solution remains elusive. Herein, we address the question of whether there is an equilibrium between diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…NMR or single molecule Förster resonance energy transfer (smFRET) have proven to be suitable tools for studying population distributions of conformational substrates in solution. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NMR or single molecule Förster resonance energy transfer (smFRET) have proven to be suitable tools for studying population distributions of conformational substrates in solution. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 Using this method, it was already shown that the DENV protease in solution is in an equilibrium between two conformations and that the presence of a competitive inhibitor stabilizes the closed conformation. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Considering these structural and functional aspects of the NS2B/NS3 pro , our research team has published several reviews 10,31,52 and original studies focused on the development of DENV and ZIKV NS2B/NS3 pro inhibitors. 53–56…”
Section: Introductionmentioning
confidence: 99%
“…25 In the antiviral work category, Goẗz et al employ singlemolecule FRET in solution to reveal the dynamics of the dengue virus protease, which is an appealing antiviral target because it takes multiple conformations at equilibrium that can be shifted with the aid of inhibitors. 26 Because of area expansion of virus vectors caused by climate change, the dengue virus and related flaviviruses are an increasing global health concern. In the same category enters the Lassa virus, a pathogen from West Africa responsible for lethal hemorrhagic fever.…”
mentioning
confidence: 99%